Diagnosis of chronic disease during admission for emergency general surgery: a portal to healthcare - Catherine Garrison Velopulos; Quintin W O Myers; Kaitlyn Dickinson; Victoria Clair; Denise M Garofalo; Ariel Wolf; Charlotte Heron; Samuel K Mathai; India V Bonner (Trauma Surgery & Acute Care Open)
Background Although nearly half of the US population has a chronic disease, many remain undiagnosed, leading to significant morbidity and mortality. Sociodemographic factors affect access to preventative healthcare, increasing rates of undiagnosed chronic disease. We hypothesize that emergency general surgery (EGS) is an important access point into the healthcare system and sought to characterize factors impacting the new diagnosis of chronic disease during admission for EGS.Methods This was a Level III retrospective cohort study conducted at a single, academic institution. Patients undergoing EGS intervention, including colectomies, cholecystectomy, hernia repair, and peptic ulcer surgeries, were identified during 2018–2019. Univariate descriptive statistics and bivariate analyses were conducted, with χ2 tests for categorical variables and Mann-Whitney U tests for continuous variables. We finally conducted a multivariable logistic regression to identify important factors related to the diagnosis of a new chronic disease.Results A total of 978 patients were included. Of these, 42.7% received a new diagnosis of chronic disease during their EGS admission. The most common diagnoses were gastroesophageal reflux disease (n=120), obesity (n=116), type 2 diabetes (n=60), and hypertension (n=48). No significant associations were found with sociodemographic factors or prior healthcare visits. Length of stay was significantly longer for those with new diagnoses (p<0.001).Conclusions Hospital admissions for EGS present a critical opportunity to identify undiagnosed chronic conditions, particularly in patients with limited healthcare access. Length of stay was associated with an increased likelihood of diagnosis. These findings suggest that emergency surgical care can serve as a gateway to preventive care. This study provides Level III evidence of the role of emergency general surgery in chronic disease diagnosis.Level of evidence III